Multilevel Governance and Adaptation of the GSTC International Regime in the Implementation of the Sigending Area Development Policy - Regiyani, Jesicha Ajeng; Amin, Khoirul; Farauqi, Mohamad Dziqie Aulia Al (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the dynamics of Multilevel Governance (MLG) in the implementation of the Sigending Ecotourism development policy and to examine how the Global Sustainable Tourism Council (GSTC) international standards are adapted at the local level in Teluk Sulaiman Village. The study uses a descriptive qualitative approach with a case study strategy through in-depth interviews, observations, document studies, and data triangulation. Informants consisted of village and district governments, Pokdarwis, FORLIKA, and conservation NGOs. The results show that Sigending's governance has mixed MLG characteristics with a predominance of type II, marked by overlapping authorities, dependence on non-state actors, and limited technical capacity in the village. GSTC standards have not been socialized and have not been translated into regional technical instruments or village SOPs, resulting in a translation gap between global norms and local implementation. At the district level, tourism policies do not yet provide operational guidelines based on GSTC indicators, while at the village level, regulations are still in draft form and monitoring mechanisms are not yet based on sustainability standards. In conclusion, the successful implementation of sustainable ecotourism in Sigending requires formal cross-level integration, the development of GSTC technical guidelines at the district level, capacity building in villages, and permanent multi-actor coordination mechanisms.